Redistribution of Forms of Potassium in Soils upon Submergence in Alfisols, Inceptisols and Entisols - Tarik Mitran and Biswapati Mandal, Pabitra Kumar Mani (Journal of the Indian Society of Soil Science, 2016)
Redistribution of forms of potassium (K) viz., water soluble, exchangeable, non-exchangeable, step-K and constant rate-K upon submergence in nine soils having contrasting properties and representing Alfisols, Inceptisols and Entisols orders were studied under laboratory condition. Soil samples (10.0 g each) were incubated under submergence (5.0 Â± 0.5 cm standing water) in tubes (15.0 cm height Ã— 2.5 cm diameter) for 30 days. Submergence caused significant increases in water soluble, non-exchangeable and step-K in all the soils over their initial values with a concomitant decrease in exchangeable K except in Entisols where it recorded an increase. On an average, the magnitude of increase in the three forms was highest in Entisols but lowest in Alfisols. Cation exchange capacity and clay content showed significant positive correlation with both the decrease in exchangeable (r = 0.95** and 0.92**) and increase in step-K (r = 0.54* and 0.58*) and showed significant negative correlation with increases in non-exchangeable K (r = -0.93** and -0.92**) content of the soils upon submergence. The results indicated the dominant role played by clay in the changes in forms of K in soils upon submergence.